An Empirical Study on Data Reuse Intention among Social Science Researchers in Chengdu, Sichuan Province, China - Chena, Xiang; Suesaowaluk, Poonphon (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
This study investigates the influencing factors of social science researchers’ intention to reuse data in Chengdu, Sichuan Province, China. The conceptual framework includes information quality, service quality, subjective norms, data repository, perceived effort, and intention to reuse data. The researchers conducted a quantitative method to distribute the online questionnaire to 500 social science researchers. The sample techniques were purposive, quota, and convenience sampling. Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) were used to analyze the data and examine the research hypotheses. The findings show that information quality, service quality, subjective norms, perceived usefulness, perceived ease of use, and attitudes to data reuse significantly impact social science researchers’ intention to reuse data. In contrast, data repository has no significant impact on social science researchers’ intention to reuse data influences. It can effectively support the cycle between data sharing and reuse in the humanities and social sciences to promote the formation of ecology and provide references and suggestions for data management in this field.